Morphological Composition of z ~ 0.4 Groups: The Site of S0 Formation - Wilman, D. J; Oemler, A; Mulchaey, J. S; McGee, S. L; Balogh, M. L; Bower, R. G (The Astrophysical journal, 2009)
The low-redshift universe (z 0.5) is not a dull place. Processes leading to the suppression of star formation and morphological transformation are prevalent: this is particularly evident in the dramatic upturn in the fraction of S0-type galaxies in clusters. However, until now, the process and environment of formation remained unidentified. We present a morphological analysis of galaxies in the optically-selected (spectroscopic friends-of-friends) group and field environments at z ~ 0.4. Groups contain a much higher fraction of S0s at fixed luminosity than the lower density field, with >99.999% confidence. Indeed, the S0 fraction in groups is at least as high as in z ~ 0.4 clusters and X-ray-selected groups, which have more luminous intragroup medium (IGM). An excess of S0s at >=0.3h -1 75 Mpc from the group center with respect to the inner regions, existing with 97% confidence at fixed luminosity, tells us that formation is not restricted to, and possibly even avoids, the group cores. Interactions with a bright X-ray-emitting IGM cannot be important for the formation of the majority of S0s in the universe. In contrast to S0s, the fraction of elliptical galaxies in groups at fixed luminosity is similar to the field, while the brightest ellipticals are strongly enhanced toward the group centers (greater than 99.999% confidence within 0.3h -1 75 Mpc). Interestingly, while spirals are altogether less common in groups than in the field, there is also an excess of faint, Sc+ type spirals within 0.3h -1 75 Mpc of the group centers (99.953% confidence). We conclude that the group and subgroup environments must be dominant for the formation of S0 galaxies, and that minor mergers, galaxy harassment, and tidal interactions are the most likely responsible mechanisms. This has implications not only for the inferred preprocessing of cluster galaxies, but also for the global morphological and star formation budget of galaxies: as hierarchical clustering progresses, more galaxies will be subject to these transformations as they enter the group environment.